Mutations in the Two-Component GluS-GluR Regulatory System Confer Resistance to β-Lactam Antibiotics in Burkholderia glumae - Marunga, Joan; Goo, Eunhye; Kang, Yongsung; Hwang, Ingyu (Frontiers in Microbiology, 2021)
Bacteria have specific signaling systems to overcome selective pressure, such as exposure to antibiotics. The two-component system (TCS) plays an important role in the development of antibiotic resistance. Using the rice pathogen Burkholderia glumae BGR1 as a model organism, we showed that the GluS (BGLU_1G13350)–GluR (BGLU_1G13360) TCS, consisting of a sensor kinase and response regulator, respectively, contributes to β-lactam resistance through a distinct mechanism. Inactivation of gluS or gluR conferred resistance to β-lactam antibiotics in B. glumae, whereas wild-type (WT) B. glumae was susceptible to these antibiotics. In gluS and gluR mutants, the expression of genes encoding metallo-β-lactamases (MBLs) and penicillin-binding proteins (PBPs) was significantly higher than in the WT. GluR-His bound to the putative promoter regions of annotated genes encoding MBL (BGLU_1G21360) and PBPs (BGLU_1G13280 and BGLU_1G04560), functioning as a repressor. These results demonstrate that the potential to attain β-lactam resistance may be genetically concealed in the TCS, in contrast to the widely accepted view of the role of TCS in antibiotic resistance. Our findings provide a new perspective on antibiotic resistance mechanisms, and suggest a different therapeutic approach for successful control of bacterial pathogens.